(untitled) - RAHMAN, ARIF (Language Horizon: Journal of Language Studies, 2014)
Terms of Address Used by Students of English Courses in Kampong Inggris Pare – Kediri Arief Rakhman English Literature Faculty of Languages and Arts State University of Surabaya Ariphdecf9@gmail.com Slamet Setiawan English Department Faculty of Languages and Arts State University of Surabaya S.setiawan@unesa.ac.id Abstract This study investigates the terms of address used by the students of english courses in Kampong Inggris Pare-Kediri. The students use various address terms which are considered as polite terms, familiar terms, and terms which show great intimacy. Unfortunately, the terms which are used to show great intimacy as considered as a terms which are less polite. It is because the terms do not refer to their real name but, the terms refer to animal or another thing. Besides, the addressee sometimes feel angry when the terms are used both in formal and informal condition. To be able to answer the research questions, this study uses the theory by Brown and Ford in Wardaugh (2006: 268-269), Kartomiharjo in Arini (2008: 17), Brown and Gilman in Wardaugh (2006: 260-261), Dunkling (1990: 11), and Stockwell (2002: 23). This study uses descriptive qualitative method. To get data, this study uses observation and intervies as data collection technique. This study found the common address terms used by the students of english courses in Kampong Inggris Pare – Kediri are first name (FN), last name (LN), titles, title + first name (TFN), title + last name (TLN), , kinship term, nickname or pet name, and endearment term. The social factors which influence the term choice are sex, familiarity, status, age, relationship and situation (formal and informal). The addressees’ assumptions about the address terms are considered as polite, familiar and, terms which are used to show great intimacy. Unfortunately, the nicknames or pet name which they use, such as Tombro, Gendut, Siung, Totok, etc, are considered as impolite terms or pronouns. It is because the terms do not have appropriate reference, in which the terms which should refer to animal or another thing refer to person. Keywords: Address Terms, Sociolinguistics Relations, Politeness in Address Terms, Power and Solidarity INTRODUCTION As human being, we need to communicate with the other people. To do this, we need a tool which is called language. When we communicate with the other people, we involve address terms to call our interlocutors. According to Brown and Ford in Wardaugh (2006: 268-269), address terms contain ‘first name, last name, title alone, multiple names, nickname or pet name, kinship terms and zero name.’ Holmes (2001: 224) stated that in using those kinds of terms, it depends on the relationship between the participants. In using address terms, the addressor can use different address terms for an addressee. The usage of those address terms are influenced by some factors. One of the factors is the relationship and intimacy between the addressor and the addressee as has been explained above. Other factors which influence the usage of the address terms are situations; formal and informal, status and age. Various intimate address terms are found in Kampong Inggris Pare. Kampong Inggris Pare is regency which is placed in Kadiri, Eas Java. Based on survey in 2012, Pare has around 128 English Courses in two villages, Tulungrejo and Palem. Because of those, this area is famous with a name of Kampoeng Inggris. In this area, there are various intimate address terms which are used by the students of English courses in addressing each other which are unique and interesting based on intimacy. For example, a student who names “Nanang” is called “Tombro” by his roommate. In this case, the address term used to address Nanang does not refer to his real name. It instead refers to kind of animal which is similar to gold fish. Another example is a student who names “Cahya”. He is called “Gendut” by his roommate and some of his friends who are closed to him. In this case, they use “Gendut” to address Cahya because Cahya is fat. Gendut is a word of Javanese which has meaning “Fat” in English. Based on those two examples above, the phenomenon which occurs in Kampong Inggris Pare shows that the address terms used by students for mockery do not have appropriate reference. Besides, it is also indicated as a way which is less polite to address someone. It can be seen in (Dunkling, 1990: 11) statement below. One feature which begins to emerge from the examples of abusive terms (bitch, chick, cow) so far quoted is that human being are frequently compared to animals. This can be certainly considered as unfriendly terms of address. For this reason, this study is conducted to reveal what the addressee fells when the addressor uses the address terms and what possible factors which influence the usage of the address terms used by the students of English course in Kampong Inggris Pare. While, the reason why this study chooses the students of Kampong Inggris Pare as the source of data is because the students come from various cities, but they study together, stay in boarding house together or dormitory together and, live in Kampong Inggris Pare together. For those reasons, they have a great intimacy and make varieties of intimate address terms which are unique and interesting. Based on the problem above, this study reaches three research questions. They are, what common address terms used by the students of English Courses in Kampong Inggris Pare, what factors possibly influence the students in choosing the address terms, and what the addressors’ and addressees’ assumption about the address terms is. The project had four related research goals to be addressed following the importance of the research described in above section, namely; to describe the common address terms which are used by the students of English Courses in Kampoeng Inggris Pare, to reveal the factors possible influence the students in choosing the address terms, to know the addressors’ and addressees’ assumption about the address terms. This study uses some theories related to the research questions. Address terms in this study refer to words used to address someone which are related to power and solidarity concept of Brown and Gilman in Wardaugh (2006: 260-261) and then analyzed by Brown and Ford in Wardaugh (2006: 268-269) in their research which consists of First Name (FN), TFN/LN, Titles (T), Last Name (LN), multiple names, nickname or pet name, and kinship term. While, there are 9 social factors which influence the choice in determining address terms in this study, which are explained by Kartomiharjo (in Arini, 2008: 17). They are Situation (formal and informal situation), Ethnics, Kinship, Familiarity, Status, Age, Sex, Marital, Place of Origin. Then, there are some polite (V) and familiar terms (T) used to address someone which is governed by the dimension of power and solidarity in this study, which are explained by Brown and Gilman in Wardaugh (2006: 260-261). Finally politeness in address terms is illustrated by Dunkling (1990: 11) and Stockwell (2002: 23). This study shows the descriptions of address terms used by students of English courses in Kampoeng Inggris Pare. Studying and understanding about address terms will lead to an understanding of politeness in addressing someone in a community. Through this study, the reader will learn knowledge about address terms which is polite and rude. It is expected to be able to provide better understanding about address terms as one of sociolinguistics materials. Moreover, this study contributes a good understanding about the factors that are possibly influence the choice of address terms, especially in Kampoeng Inggris Pare. The most important thing is this study shows whether the address terms used by the students of English courses in Kampong Inggris Pare are considered as polite terms or less polite terms. RESEARCH METHOD This study uses the descriptive qualitative method. Descriptive qualitative is the most appropriate method for this study. It is because this study reveals a phenomenon which occurs among the society, particularly among the students of English courses who stay in an area which is called Kampong Inggris Pare. The data of the descriptive qualitative is not in number but tends to interpret a subject or phenomenon in form of words or sentences. Litosseliti (2010: 52) states that qualitative research is concerned with structure and patterns, and how something is. Descriptive method is used to search problems which occur in society. This method tries to reveal a phenomenon comprehensively and based on file collection. Whitney in (Arini, 2008: 26) explains that descriptive method is a fact search using an appropriate interpretation. The data of this study are in form of utterances and sentences which are noted during observation and interview. The source of data is the utterances produced by the students of English courses in Kampong Inggris Pare which contained the address terms, social factors which influence the term choice, the addressee’s assumption about the address terms, and other utterances which are related to them. In the process of collecting data, the researcher uses two data collection techniques. They are observation and interview. In order to be able to answer research question no. 1 about the common address terms used by the students in Kampoeng Inggris – Pare, this study uses observation as data collection technique. Meanwhile, this study also uses interview to obtain the detailed data. The interview is conducted in order to get more varieties about the address terms, and be able to answer research questions no. 2 and 3 about the factors which influence the students in choosing the address terms and the addressors’ and addressees’ assumption about the address terms. After the data has been collected, this study analyzes the data. This study uses data analysis technique by Miles and Huberman (1994: 10) which mention three steps in analysing qualitative data. They are data reduction, data display and conclusion drawing and verification. RESULT AND DISCUSSION This study found that the address term used by the students of English courses in Kampong Inggris Pare include first name (FN) like ‘Erwin, Yoga’, last name (LN) like ‘Salwa, Sari’, titles, title + first name (TFN) like ‘Ms. Uswatun’, title + last name (TLN) like ‘Mrs. Dhani’, kinship term ‘bro’, nickname or pet name ‘Tombro, Gendut, Monyet’, and endearment term ‘honey, babe’ which every term is influenced by certain factor. The factors which influence the students of English courses in Kampong Inggris Pare in choosing the address terms are sex, familiarity, status, age, relationship, and situation (formal and informal). Different sex must use different terms of address. For example the students use the term ‘Mr’ to address male and ‘Ms’ to address female. The terms ‘Mr and Ms’ are also used by the students to address their friends who they have just acquainted. While TFN and TLN ‘Ms. Uswatun and Mrs. Dhani’ are used to address some students who are older and have higher status. The other factor which influences the students in choosing the address term is situation. In formal condition the students may use first name (FN), last name (LN) or TFN and TLN, but in informal situation they may use kinship terms, endearment terms or nickname or pet name. The use of those three kinds of address terms are also influenced by relationship, particularly greater intimacy. The students of English courses in Kampong Inggris Pare use three kinds of address terms which are considered as polite, familiar terms, and the terms which show great intimacy. The polite terms used by the students include title alone, TFN, and TLN. While, the familiar terms used include FN and LN. At last, the terms which show great intimacy include kinship term, nicknames or pet names, and endearment terms. Familiar Terms The students use FN and LN because some students are familiar with their first names and some others are familiar with their last names. For example two students named Erwin Jatmiko and Yoga Ferian are called Erwin and Yoga by their friends. They admitted there are some other friends who also named Yoga, so that the name becomes familiar. According to Brown and Ford in Wardaugh (2006: 268-269) FN shows equality and familiarity. Equality means we have similarity in status and age. For example people who work together have same positions and age. They are required to use FN. While familiarity means we know someone’s background or knowledge of someone whom we know. It can be our close friend. Based on The study by Brown and Gilman in Wardaugh (2006: 260-261) which explained about the distinction between tu-vous (T/V) which governed by two aspects called power and solidarity. FN and LN which are used by the students are considered as T form or familiar forms which are governed by social distance. Based on those three explanations above, it can be concluded that factor which influence the students in using FN and LN is similar to the factors which influence addressors in using FN by Brown and Ford in Wardaugh (2006: 268-269). If the students use FN and LN because some of their first names of last names are familiar, addressors use FN because the addressors and the addressee have familiar or known their background one another and have same position and age. Both FN and LN are considered as T form or familiar forms which are governed by social distance. Polite Terms The polite terms used by the students include titles, TFN, and TLN. Titles (Mr. and Ms) are the polite term used to express their distant or loaf relationship. For example, when they want to address their friends whom they have just acquainted, they prefer to use Mr. for male and Ms. for female. According to Brown and Ford in Wardaugh (2006: 268), addressing by titles like Sir, Madam, Mr. /Ms. is the least intimate term of address. When the relationship between the addressors and the addressee is not intimate or they do not know each other they use this kind of address term. This shows that distant relationship becomes a factor which influences the addressor to choose these terms. According to Kartomihardjo in Arini (2008: 17), relationship between the addressor and the addressee becomes one of social factors which influence the addressors to determine the terms of address. Brown and Gilman in Wardaugh (2006: 260-261) explained that people who don’t know each other tend to use vous (V) in addressing each other. This indicates the social distance between the participants. The use of vous (V) can change to tu (T) when their relationships become closer or more intimate. Besides, the students also used TFN and TLN as polite terms. Those kinds of address terms are the polite terms used to show respect and politeness to their friends who are older and have higher status. For example some students address their friend Ms. Uswatun and Mrs. Dhani. The students said that because Ms.Uswatun and Mrs. Dhani were older and had higher status than they did. The terms indicate inequality in status and age. According to Brown and Ford in Wardaugh (2006: 268), TLN/FN indicates that the addressee has higher status than the addressor. The students use V to address Ms.Uswatun or Mrs.Dhani, and receive T. This indicates that both of the students have power, which those two students who have higher status use T to address the lower status, but they receive V. Brown and Gilman in Wardaugh (2006: 261) explained that power is usually indicated in the form of social status. A person who has a higher status in society may call someone of lower status by his first name only, but he/she receives title + last name (TLN). This indicates that someone of lower status call a person who has a higher status with TLN to show his respect or inequality in status or power. The terms which show great intimacy The terms used by the students to show great intimacy includes kinship term (bro), nicknames or pet names (Tombro, Gendut, Paijo, etc), and endearment terms (honey and babe). According to Brown and Ford in Wardaugh (2006: 268-269), kinship system and pet name are used to show the greater intimacy between the participants. When a John Smith’s mother calls him with nickname (Johnny), or pet name (honey) and she receives kinship term (mom). It signs that his mother indicates the greater intimacy to him. From those explanations, it can be seen that the intimate relationship becomes the factor which influences the addressor to use those three kinds of address terms. The greater intimacy between the students makes them produce various nicknames such as Tombro, Gendut, Paijo, etc. When a student calls his friend with pet name (Tombro), he receives nickname (Gendut). The students assumed that these kinds of address terms are considered as less polite terms of address, but they still use it for mockery. Besides, the addressees are frequently angry or not feeling comfortable when they are addressed with those terms. According to Dunkling (1990: 11) it is generally true to say that insulting terms or vocative expressions (you bloody fool, you old cow, you bitch, etc) are more likely to be unfriendly than friendly, although they can be turned into covert endearments if said in a particular way in a particular context. Another reason for considering that the nicknames or pet name used by the students as less polite terms, It is because the terms do not have appropriate reference, in which the term which should refer to animal (Tombro) or part of body (Siung) refer to person. A problem which emerges from what occurs in the phenomenon is that human being is considered with animal. Dunkling (1990: 11) stated that One feature which begins to emerge from the examples of abusive terms (bitch, chick, cow) so far quoted is that human being are frequently compared to animals. This can be certainly considered as unfriendly terms of address. In summary, the address terms used by the students are grouped into two. They are polite pronoun or vous (V), and the terms which show familiarity and intimacy or known as tu (T). The (V) forms used by the students include titles, TFN, and TLN. The (T) forms which show familiarity include FN, LN, while kinship term, nicknames or pet names, and endearment terms are to show great intimacy. Unfortunately, the nicknames or pet name which they use are considered as less polite terms. It is because the terms do not have appropriate reference, in which the terms which should refer to another thing or animal refer to person. CONCLUSSION This study found that the common address terms used by the students of English courses in Kampong Inggris Pare – Kediri are first name (FN), last name (LN), titles, title + first name (TFN), title + last name (TLN), kinship term, nickname or pet name, and endearment term. Those kinds of address terms are closed to the study by Brown and Ford in Wardaugh (2006:268-269) in their pattern about address terms are titles (T), First Name (FN), Last Name (LN), TFN/LN, Multiple Names, Nickname or pet name, Kinship term, and zero name (q). The social factors which influence the students in determining the terms of address are sex, familiarity, status, age, relationship and situation (formal and informal). Those factors are closest to the study by Kartomiharjo (in Arini, 2008: 17), which mention 9 social factors in determining the choice of address terms. They are Situation (formal and informal situation), Ethnics, Kinship, Familiarity, Status, Age, Sex, Marital, and Place of Origin. The address terms used by the students are grouped into two. They are the address terms which are considered as polite pronoun or vous (V), and the terms which show familiarity and intimacy or known as tu (T). The polite terms used by the students include title alone, TFN, and TLN. While, the familiar terms used include FN and LN. At last, the terms which show great intimacy include kinship term, nicknames or pet names, and endearment terms. It is supported through the study by Brown and Gilman in Wardaugh (2006: 260-261) who explained that tu (T) form is the ‘familiar’ form which is used to show familiarity and intimacy between the participants. While vous (V) form is the ‘polite’ form which is used to show politeness and respect to someone older, has higher status, and distant relationship. Unfortunately, the nicknames or pet name which they use such as Tombro, Gendut, Siung, Totok, etc, are considered as less polite terms or pronouns. It is because the terms do not have appropriate reference, in which the terms which should refer to another thing or animal refer to person. Dunkling (1990: 11) stated that One feature which begins to emerge from the examples of abusive terms (bitch, chick, cow) so far quoted is that human being are frequently compared to animals. This can be certainly considered as unfriendly terms of address. In a certain condition, sometimes the addressee feels angry when the terms are used both in formal and informal condition, because the addressee feels that the terms for mockery or insulting terms. According to Dunkling (1990: 11) it is generally true to say that insulting terms or vocative expressions (you bloody fool, you old cow, you bitch, etc) are more likely to be unfriendly than friendly. Based on the explanation about the diagram above, Nicknames or pet names which are used by the students, such as Tombro, Gendut, Paijo, Totok, Siung, Brewok, etc do not have appropriate reference. It is because the terms which should refer to another thing or animal refer to person. SUGGESTION When choosing and using a term to address another person, the speaker’s intention is not only to establish good communication but also to initiate and show some type of relations with the listener. People have different ways to indicate who is talking (the speaker) and whom he is talking to (the listener). If the ’participants’ relation is close, they will use another appropriate term. According to Brown and Ford (1961), the relationship between addresser and addressee can be seen through their use of address terms whether it is intimate or aloof (distant). Behaving politely is a good way or attitude to make other people feel respected and comfortable (Brown and Levinson 1987: 129). For that reason, addressing someone with the most appropriate and polite term will show that we really respect them, particularly to someone who is older and has higher status than we (are). Dealing with nicknames and pet names which are used by the students, it is better for them not to use those kinds of address terms. It is because the address terms are less polite. They can address their close friends with nickname which was still related to their real names, such as FN, LN, FNLN, kinship term, or the terms which do not mention the lack of the addressee. Stockwell (2002: 23) states that politeness in the case of addressing term can be indicated by using title, first name, last name, or by combination of them (TLN, TFN, FNLN). REFERENCE Adamic, L. (1942) What’s your name? New York: Harper. Arini, Syahadah. (2012). Addressing Terms Used By Helmer and Nora in HenrikIbsen’s A Doll House. Skripsi S-1, Unpublished-English Department Faculty of Language and Art. State University of Surabaya. Bonvillain, Nancy (2003). Language, Culture, and Communication: The Meaning of Messages (4th edn. ed.). Upper Saddle River, N.J.: Prentice Hall. Braun, Friederike. (1988). Terms of Address: Problems of Patterns and Usage in Various Languages and Cultures. Mouton de Gruyter, Berlin. Brown, Penelope and Stephen C. Levinson, (1987). Politeness and Some Universal in Language Usage. New York: Cambridge University Press. Chaer, Abdul. (1988). Tata Bahasa Praktis Bahasa Indonesia. Jakarta: Bhratara Karya Aksara. Dunkling, Leslie. (1988). A dictionary of epithets and terms if address. Routledge, London; New York. Fasold, Ralph. (1990). The Sociolinguistics of Language. USA: Basil Blackwell Inch. Holmes, J. (2001). Learning About Language: An Introduction to Sociolinguistics. London/New York: Longman; Pearson Longman. Hadi, Cipung Bayu. (2006). The Address System Used by The Karang People. Skripsi S-1, Unpublished-English Department Faculty of Language and Art. State University of Surabaya. Leech, N. Geoffrey and Short, Michael H. (1984). Style in Fiction. New York: Longman Litosseliti, Lia. (2010). Research Methods in Linguistics. Great Britain: MPG Books Group. Miles, M. B., & Huberman, A. M. (1994). An Expanded Sourcebook Qualitative Data Analysis. Thousand Oaks, CA: Sage Publications. Mesthrie, R. (2001). Concise Encyclopedia of Sociolinguistics. Elsevier Science Ltd, The Boulevard, Langford Lane, Kidlington, Oxford OX5 1GB, UK Nasution, M. Dj dkk. (1994). Sistem sapaan Dialek Jakarta. Jakarta: Departemen Pendidikan dan Kebudayaan. Sulastri. (2009). Study of Addressing Terms in ‘A Work of Art’ and The Robbers’ by Anton Chekhov. Skripsi S-1, Unpublished-English Department Faculty of Language and Art. State University of Surabaya. Stockwell, Peter. (2002). Sociolinguistics. London. Routledge. Spolsky, Bernard. (1998). Sociolinguistics. New York: Oxford University Press. Stageberg, N. C., & Anderson, W. L. (1967). Readings on Semanitcs [compiled By] Norman C. Stageberg [and] Wallace L. Anderson: Holt, Rinehart and Winston. Sugiyono. (2010). Metode Penelitian Kuantitatif Kualitatif dan R&D. Bandung: Alfabeta. Wardhaugh, Ronald. (2006). An Introduction to sociolinguistic 5th Edition. Australia: Blackwell publishing. Wray, Alison, et al. (1998). Project in Linguistics: A Practical Guide to Research Language. Print. Yule, G. 2006. The study of language. Third Edition. USA: Cambridge University Press. Yule, G. (1996). The Study of Language. Third Second. USA: Cambridge University Press. Terms of Address Used by Students of English Courses in Kampong Inggris Pare – Kediri Arief Rakhman English Literature Faculty of Languages and Arts State University of Surabaya Ariphdecf9@gmail.com Slamet Setiawan English Department Faculty of Languages and Arts State University of Surabaya S.setiawan@unesa.ac.id Abstract This study investigates the terms of address used by the students of english courses in Kampong Inggris Pare-Kediri. The students use various address terms which are considered as polite terms, familiar terms, and terms which show great intimacy. Unfortunately, the terms which are used to show great intimacy as considered as a terms which are less polite. It is because the terms do not refer to their real name but, the terms refer to animal or another thing. Besides, the addressee sometimes feel angry when the terms are used both in formal and informal condition. To be able to answer the research questions, this study uses the theory by Brown and Ford in Wardaugh (2006: 268-269), Kartomiharjo in Arini (2008: 17), Brown and Gilman in Wardaugh (2006: 260-261), Dunkling (1990: 11), and Stockwell (2002: 23). This study uses descriptive qualitative method. To get data, this study uses observation and intervies as data collection technique. This study found the common address terms used by the students of english courses in Kampong Inggris Pare – Kediri are first name (FN), last name (LN), titles, title + first name (TFN), title + last name (TLN), , kinship term, nickname or pet name, and endearment term. The social factors which influence the term choice are sex, familiarity, status, age, relationship and situation (formal and informal). The addressees’ assumptions about the address terms are considered as polite, familiar and, terms which are used to show great intimacy. Unfortunately, the nicknames or pet name which they use, such as Tombro, Gendut, Siung, Totok, etc, are considered as impolite terms or pronouns. It is because the terms do not have appropriate reference, in which the terms which should refer to animal or another thing refer to person. Keywords: Address Terms, Sociolinguistics Relations, Politeness in Address Terms, Power and Solidarity INTRODUCTION As human being, we need to communicate with the other people. To do this, we need a tool which is called language. When we communicate with the other people, we involve address terms to call our interlocutors. According to Brown and Ford in Wardaugh (2006: 268-269), address terms contain ‘first name, last name, title alone, multiple names, nickname or pet name, kinship terms and zero name.’ Holmes (2001: 224) stated that in using those kinds of terms, it depends on the relationship between the participants. In using address terms, the addressor can use different address terms for an addressee. The usage of those address terms are influenced by some factors. One of the factors is the relationship and intimacy between the addressor and the addressee as has been explained above. Other factors which influence the usage of the address terms are situations; formal and informal, status and age. Various intimate address terms are found in Kampong Inggris Pare. Kampong Inggris Pare is regency which is placed in Kadiri, Eas Java. Based on survey in 2012, Pare has around 128 English Courses in two villages, Tulungrejo and Palem. Because of those, this area is famous with a name of Kampoeng Inggris. In this area, there are various intimate address terms which are used by the students of English courses in addressing each other which are unique and interesting based on intimacy. For example, a student who names “Nanang” is called “Tombro” by his roommate. In this case, the address term used to address Nanang does not refer to his real name. It instead refers to kind of animal which is similar to gold fish. Another example is a student who names “Cahya”. He is called “Gendut” by his roommate and some of his friends who are closed to him. In this case, they use “Gendut” to address Cahya because Cahya is fat. Gendut is a word of Javanese which has meaning “Fat” in English. Based on those two examples above, the phenomenon which occurs in Kampong Inggris Pare shows that the address terms used by students for mockery do not have appropriate reference. Besides, it is also indicated as a way which is less polite to address someone. It can be seen in (Dunkling, 1990: 11) statement below. One feature which begins to emerge from the examples of abusive terms (bitch, chick, cow) so far quoted is that human being are frequently compared to animals. This can be certainly considered as unfriendly terms of address. For this reason, this study is conducted to reveal what the addressee fells when the addressor uses the address terms and what possible factors which influence the usage of the address terms used by the students of English course in Kampong Inggris Pare. While, the reason why this study chooses the students of Kampong Inggris Pare as the source of data is because the students come from various cities, but they study together, stay in boarding house together or dormitory together and, live in Kampong Inggris Pare together. For those reasons, they have a great intimacy and make varieties of intimate address terms which are unique and interesting. Based on the problem above, this study reaches three research questions. They are, what common address terms used by the students of English Courses in Kampong Inggris Pare, what factors possibly influence the students in choosing the address terms, and what the addressors’ and addressees’ assumption about the address terms is. The project had four related research goals to be addressed following the importance of the research described in above section, namely; to describe the common address terms which are used by the students of English Courses in Kampoeng Inggris Pare, to reveal the factors possible influence the students in choosing the address terms, to know the addressors’ and addressees’ assumption about the address terms. This study uses some theories related to the research questions. Address terms in this study refer to words used to address someone which are related to power and solidarity concept of Brown and Gilman in Wardaugh (2006: 260-261) and then analyzed by Brown and Ford in Wardaugh (2006: 268-269) in their research which consists of First Name (FN), TFN/LN, Titles (T), Last Name (LN), multiple names, nickname or pet name, and kinship term. While, there are 9 social factors which influence the choice in determining address terms in this study, which are explained by Kartomiharjo (in Arini, 2008: 17). They are Situation (formal and informal situation), Ethnics, Kinship, Familiarity, Status, Age, Sex, Marital, Place of Origin. Then, there are some polite (V) and familiar terms (T) used to address someone which is governed by the dimension of power and solidarity in this study, which are explained by Brown and Gilman in Wardaugh (2006: 260-261). Finally politeness in address terms is illustrated by Dunkling (1990: 11) and Stockwell (2002: 23). This study shows the descriptions of address terms used by students of English courses in Kampoeng Inggris Pare. Studying and understanding about address terms will lead to an understanding of politeness in addressing someone in a community. Through this study, the reader will learn knowledge about address terms which is polite and rude. It is expected to be able to provide better understanding about address terms as one of sociolinguistics materials. Moreover, this study contributes a good understanding about the factors that are possibly influence the choice of address terms, especially in Kampoeng Inggris Pare. The most important thing is this study shows whether the address terms used by the students of English courses in Kampong Inggris Pare are considered as polite terms or less polite terms. RESEARCH METHOD This study uses the descriptive qualitative method. Descriptive qualitative is the most appropriate method for this study. It is because this study reveals a phenomenon which occurs among the society, particularly among the students of English courses who stay in an area which is called Kampong Inggris Pare. The data of the descriptive qualitative is not in number but tends to interpret a subject or phenomenon in form of words or sentences. Litosseliti (2010: 52) states that qualitative research is concerned with structure and patterns, and how something is. Descriptive method is used to search problems which occur in society. This method tries to reveal a phenomenon comprehensively and based on file collection. Whitney in (Arini, 2008: 26) explains that descriptive method is a fact search using an appropriate interpretation. The data of this study are in form of utterances and sentences which are noted during observation and interview. The source of data is the utterances produced by the students of English courses in Kampong Inggris Pare which contained the address terms, social factors which influence the term choice, the addressee’s assumption about the address terms, and other utterances which are related to them. In the process of collecting data, the researcher uses two data collection techniques. They are observation and interview. In order to be able to answer research question no. 1 about the common address terms used by the students in Kampoeng Inggris – Pare, this study uses observation as data collection technique. Meanwhile, this study also uses interview to obtain the detailed data. The interview is conducted in order to get more varieties about the address terms, and be able to answer research questions no. 2 and 3 about the factors which influence the students in choosing the address terms and the addressors’ and addressees’ assumption about the address terms. After the data has been collected, this study analyzes the data. This study uses data analysis technique by Miles and Huberman (1994: 10) which mention three steps in analysing qualitative data. They are data reduction, data display and conclusion drawing and verification. RESULT AND DISCUSSION This study found that the address term used by the students of English courses in Kampong Inggris Pare include first name (FN) like ‘Erwin, Yoga’, last name (LN) like ‘Salwa, Sari’, titles, title + first name (TFN) like ‘Ms. Uswatun’, title + last name (TLN) like ‘Mrs. Dhani’, kinship term ‘bro’, nickname or pet name ‘Tombro, Gendut, Monyet’, and endearment term ‘honey, babe’ which every term is influenced by certain factor. The factors which influence the students of English courses in Kampong Inggris Pare in choosing the address terms are sex, familiarity, status, age, relationship, and situation (formal and informal). Different sex must use different terms of address. For example the students use the term ‘Mr’ to address male and ‘Ms’ to address female. The terms ‘Mr and Ms’ are also used by the students to address their friends who they have just acquainted. While TFN and TLN ‘Ms. Uswatun and Mrs. Dhani’ are used to address some students who are older and have higher status. The other factor which influences the students in choosing the address term is situation. In formal condition the students may use first name (FN), last name (LN) or TFN and TLN, but in informal situation they may use kinship terms, endearment terms or nickname or pet name. The use of those three kinds of address terms are also influenced by relationship, particularly greater intimacy. The students of English courses in Kampong Inggris Pare use three kinds of address terms which are considered as polite, familiar terms, and the terms which show great intimacy. The polite terms used by the students include title alone, TFN, and TLN. While, the familiar terms used include FN and LN. At last, the terms which show great intimacy include kinship term, nicknames or pet names, and endearment terms. Familiar Terms The students use FN and LN because some students are familiar with their first names and some others are familiar with their last names. For example two students named Erwin Jatmiko and Yoga Ferian are called Erwin and Yoga by their friends. They admitted there are some other friends who also named Yoga, so that the name becomes familiar. According to Brown and Ford in Wardaugh (2006: 268-269) FN shows equality and familiarity. Equality means we have similarity in status and age. For example people who work together have same positions and age. They are required to use FN. While familiarity means we know someone’s background or knowledge of someone whom we know. It can be our close friend. Based on The study by Brown and Gilman in Wardaugh (2006: 260-261) which explained about the distinction between tu-vous (T/V) which governed by two aspects called power and solidarity. FN and LN which are used by the students are considered as T form or familiar forms which are governed by social distance. Based on those three explanations above, it can be concluded that factor which influence the students in using FN and LN is similar to the factors which influence addressors in using FN by Brown and Ford in Wardaugh (2006: 268-269). If the students use FN and LN because some of their first names of last names are familiar, addressors use FN because the addressors and the addressee have familiar or known their background one another and have same position and age. Both FN and LN are considered as T form or familiar forms which are governed by social distance. Polite Terms The polite terms used by the students include titles, TFN, and TLN. Titles (Mr. and Ms) are the polite term used to express their distant or loaf relationship. For example, when they want to address their friends whom they have just acquainted, they prefer to use Mr. for male and Ms. for female. According to Brown and Ford in Wardaugh (2006: 268), addressing by titles like Sir, Madam, Mr. /Ms. is the least intimate term of address. When the relationship between the addressors and the addressee is not intimate or they do not know each other they use this kind of address term. This shows that distant relationship becomes a factor which influences the addressor to choose these terms. According to Kartomihardjo in Arini (2008: 17), relationship between the addressor and the addressee becomes one of social factors which influence the addressors to determine the terms of address. Brown and Gilman in Wardaugh (2006: 260-261) explained that people who don’t know each other tend to use vous (V) in addressing each other. This indicates the social distance between the participants. The use of vous (V) can change to tu (T) when their relationships become closer or more intimate. Besides, the students also used TFN and TLN as polite terms. Those kinds of address terms are the polite terms used to show respect and politeness to their friends who are older and have higher status. For example some students address their friend Ms. Uswatun and Mrs. Dhani. The students said that because Ms.Uswatun and Mrs. Dhani were older and had higher status than they did. The terms indicate inequality in status and age. According to Brown and Ford in Wardaugh (2006: 268), TLN/FN indicates that the addressee has higher status than the addressor. The students use V to address Ms.Uswatun or Mrs.Dhani, and receive T. This indicates that both of the students have power, which those two students who have higher status use T to address the lower status, but they receive V. Brown and Gilman in Wardaugh (2006: 261) explained that power is usually indicated in the form of social status. A person who has a higher status in society may call someone of lower status by his first name only, but he/she receives title + last name (TLN). This indicates that someone of lower status call a person who has a higher status with TLN to show his respect or inequality in status or power. The terms which show great intimacy The terms used by the students to show great intimacy includes kinship term (bro), nicknames or pet names (Tombro, Gendut, Paijo, etc), and endearment terms (honey and babe). According to Brown and Ford in Wardaugh (2006: 268-269), kinship system and pet name are used to show the greater intimacy between the participants. When a John Smith’s mother calls him with nickname (Johnny), or pet name (honey) and she receives kinship term (mom). It signs that his mother indicates the greater intimacy to him. From those explanations, it can be seen that the intimate relationship becomes the factor which influences the addressor to use those three kinds of address terms. The greater intimacy between the students makes them produce various nicknames such as Tombro, Gendut, Paijo, etc. When a student calls his friend with pet name (Tombro), he receives nickname (Gendut). The students assumed that these kinds of address terms are considered as less polite terms of address, but they still use it for mockery. Besides, the addressees are frequently angry or not feeling comfortable when they are addressed with those terms. According to Dunkling (1990: 11) it is generally true to say that insulting terms or vocative expressions (you bloody fool, you old cow, you bitch, etc) are more likely to be unfriendly than friendly, although they can be turned into covert endearments if said in a particular way in a particular context. Another reason for considering that the nicknames or pet name used by the students as less polite terms, It is because the terms do not have appropriate reference, in which the term which should refer to animal (Tombro) or part of body (Siung) refer to person. A problem which emerges from what occurs in the phenomenon is that human being is considered with animal. Dunkling (1990: 11) stated that One feature which begins to emerge from the examples of abusive terms (bitch, chick, cow) so far quoted is that human being are frequently compared to animals. This can be certainly considered as unfriendly terms of address. In summary, the address terms used by the students are grouped into two. They are polite pronoun or vous (V), and the terms which show familiarity and intimacy or known as tu (T). The (V) forms used by the students include titles, TFN, and TLN. The (T) forms which show familiarity include FN, LN, while kinship term, nicknames or pet names, and endearment terms are to show great intimacy. Unfortunately, the nicknames or pet name which they use are considered as less polite terms. It is because the terms do not have appropriate reference, in which the terms which should refer to another thing or animal refer to person. CONCLUSSION This study found that the common address terms used by the students of English courses in Kampong Inggris Pare – Kediri are first name (FN), last name (LN), titles, title + first name (TFN), title + last name (TLN), kinship term, nickname or pet name, and endearment term. Those kinds of address terms are closed to the study by Brown and Ford in Wardaugh (2006:268-269) in their pattern about address terms are titles (T), First Name (FN), Last Name (LN), TFN/LN, Multiple Names, Nickname or pet name, Kinship term, and zero name (q). The social factors which influence the students in determining the terms of address are sex, familiarity, status, age, relationship and situation (formal and informal). Those factors are closest to the study by Kartomiharjo (in Arini, 2008: 17), which mention 9 social factors in determining the choice of address terms. They are Situation (formal and informal situation), Ethnics, Kinship, Familiarity, Status, Age, Sex, Marital, and Place of Origin. The address terms used by the students are grouped into two. They are the address terms which are considered as polite pronoun or vous (V), and the terms which show familiarity and intimacy or known as tu (T). The polite terms used by the students include title alone, TFN, and TLN. While, the familiar terms used include FN and LN. At last, the terms which show great intimacy include kinship term, nicknames or pet names, and endearment terms. It is supported through the study by Brown and Gilman in Wardaugh (2006: 260-261) who explained that tu (T) form is the ‘familiar’ form which is used to show familiarity and intimacy between the participants. While vous (V) form is the ‘polite’ form which is used to show politeness and respect to someone older, has higher status, and distant relationship. Unfortunately, the nicknames or pet name which they use such as Tombro, Gendut, Siung, Totok, etc, are considered as less polite terms or pronouns. It is because the terms do not have appropriate reference, in which the terms which should refer to another thing or animal refer to person. Dunkling (1990: 11) stated that One feature which begins to emerge from the examples of abusive terms (bitch, chick, cow) so far quoted is that human being are frequently compared to animals. This can be certainly considered as unfriendly terms of address. In a certain condition, sometimes the addressee feels angry when the terms are used both in formal and informal condition, because the addressee feels that the terms for mockery or insulting terms. According to Dunkling (1990: 11) it is generally true to say that insulting terms or vocative expressions (you bloody fool, you old cow, you bitch, etc) are more likely to be unfriendly than friendly. Based on the explanation about the diagram above, Nicknames or pet names which are used by the students, such as Tombro, Gendut, Paijo, Totok, Siung, Brewok, etc do not have appropriate reference. It is because the terms which should refer to another thing or animal refer to person. SUGGESTION When choosing and using a term to address another person, the speaker’s intention is not only to establish good communication but also to initiate and show some type of relations with the listener. People have different ways to indicate who is talking (the speaker) and whom he is talking to (the listener). If the ’participants’ relation is close, they will use another appropriate term. According to Brown and Ford (1961), the relationship between addresser and addressee can be seen through their use of address terms whether it is intimate or aloof (distant). Behaving politely is a good way or attitude to make other people feel respected and comfortable (Brown and Levinson 1987: 129). For that reason, addressing someone with the most appropriate and polite term will show that we really respect them, particularly to someone who is older and has higher status than we (are). Dealing with nicknames and pet names which are used by the students, it is better for them not to use those kinds of address terms. It is because the address terms are less polite. They can address their close friends with nickname which was still related to their real names, such as FN, LN, FNLN, kinship term, or the terms which do not mention the lack of the addressee. Stockwell (2002: 23) states that politeness in the case of addressing term can be indicated by using title, first name, last name, or by combination of them (TLN, TFN, FNLN). REFERENCE Adamic, L. (1942) What’s your name? New York: Harper. Arini, Syahadah. (2012). Addressing Terms Used By Helmer and Nora in HenrikIbsen’s A Doll House. Skripsi S-1, Unpublished-English Department Faculty of Language and Art. State University of Surabaya. Bonvillain, Nancy (2003). Language, Culture, and Communication: The Meaning of Messages (4th edn. ed.). Upper Saddle River, N.J.: Prentice Hall. Braun, Friederike. (1988). Terms of Address: Problems of Patterns and Usage in Various Languages and Cultures. Mouton de Gruyter, Berlin. Brown, Penelope and Stephen C. Levinson, (1987). Politeness and Some Universal in Language Usage. New York: Cambridge University Press. Chaer, Abdul. (1988). Tata Bahasa Praktis Bahasa Indonesia. Jakarta: Bhratara Karya Aksara. Dunkling, Leslie. (1988). A dictionary of epithets and terms if address. Routledge, London; New York. Fasold, Ralph. (1990). The Sociolinguistics of Language. USA: Basil Blackwell Inch. Holmes, J. (2001). Learning About Language: An Introduction to Sociolinguistics. London/New York: Longman; Pearson Longman. Hadi, Cipung Bayu. (2006). The Address System Used by The Karang People. Skripsi S-1, Unpublished-English Department Faculty of Language and Art. State University of Surabaya. Leech, N. Geoffrey and Short, Michael H. (1984). Style in Fiction. New York: Longman Litosseliti, Lia. (2010). Research Methods in Linguistics. Great Britain: MPG Books Group. Miles, M. B., & Huberman, A. M. (1994). An Expanded Sourcebook Qualitative Data Analysis. Thousand Oaks, CA: Sage Publications. Mesthrie, R. (2001). Concise Encyclopedia of Sociolinguistics. Elsevier Science Ltd, The Boulevard, Langford Lane, Kidlington, Oxford OX5 1GB, UK Nasution, M. Dj dkk. (1994). Sistem sapaan Dialek Jakarta. Jakarta: Departemen Pendidikan dan Kebudayaan. Sulastri. (2009). Study of Addressing Terms in ‘A Work of Art’ and The Robbers’ by Anton Chekhov. Skripsi S-1, Unpublished-English Department Faculty of Language and Art. State University of Surabaya. Stockwell, Peter. (2002). Sociolinguistics. London. Routledge. Spolsky, Bernard. (1998). Sociolinguistics. New York: Oxford University Press. Stageberg, N. C., & Anderson, W. L. (1967). Readings on Semanitcs [compiled By] Norman C. Stageberg [and] Wallace L. Anderson: Holt, Rinehart and Winston. Sugiyono. (2010). Metode Penelitian Kuantitatif Kualitatif dan R&D. Bandung: Alfabeta. Wardhaugh, Ronald. (2006). An Introduction to sociolinguistic 5th Edition. Australia: Blackwell publishing. Wray, Alison, et al. (1998). Project in Linguistics: A Practical Guide to Research Language. Print. Yule, G. 2006. The study of language. Third Edition. USA: Cambridge University Press. Yule, G. (1996). The Study of Language. Third Second. USA: Cambridge University Press.